عوامل تعزيز القدرة التنافسية للقطاع السياحي في الجزائر: دراسة تحليلية - فريحة، ليندة Farihah, Lindah; خروف، منير Kharouf, Munir (جامعة الجزائر 3 - كلية العلوم الإقتصادية والعلوم التجارية وعلوم التسيير, 2020)
نهدف من خلال هذه البحث إلى التعرف على عوامل تعزيز القدرة التنافسية للقطاع السياحي في الجزائر من خلال دراسة تحليلية لمؤشرات التنافسية ومؤشرات تنافسية السياحة والاسفار العالمية، وبسبب تراجع عائدات النفط والمحروقات تراهن الجزائر على القطاع السياحي كأحد مرتكزات التنويع الاقتصادي. ورغم سلبيات المؤشرات إلا ان المنظمة العالمية للسياحة ادرجت قطاع السياحة في الجزائر كأحد الدعائم الأساسية للنهوض بالاقتصاد الوطني وخلق تنمية اقتصادية، نظرا للإمكانيات والموارد التي تتوفر عليها الجزائر في المجال السياحي.
Through an analytical study of competitiveness indicators and competitiveness indicators of tourism and international travel, given the importance of this sector and the decline in revenues from oil and fuel, Algeria is betting on the tourism sector as one of the pillars of economic diversification. Despite the negative indicators, the World Tourism Organization has ranked the tourism sector in Algeria as one of the essential pillars of the promotion of the national economy and economic development, given the potential and the resources available to it. Algeria in the tourism sector. In Algeria.
Keywords: السياحة الجزائرية -- القدرات السياحية -- الاقتصاد الجزائري -- التنمية المستدامة